Strength of mesh augmented rotator cuff repair using finite element analysis - Ng, Nicholas Kee Wei (Nanyang Technological University, 2020)
Rotator cuff tear is a common injury and can be triggered by themost trivial of motion. Presently, there are several repair techniquesfor rotator cuff repair, such as suture techniques, superior capsular reconstruction and mesh augmentation repair, which will be discussed in detail. Despite the various alternatives available, each of these techniques come withlimitations., often resulting in a re-tear of rotator cuff tendons. Therefore, this report evaluates the methods usedand the effect of mesh repair. Previous years’ reports used goat shoulders where the specimens undergo loading.However, due to several issues, it will be conducted via Finite Element Analysis(FEA)of human shoulders.